2018
DOI: 10.1177/1354856518808936
|View full text |Cite
|
Sign up to set email alerts
|

E-books: In the shadow of print

Abstract: The e-book has gained a large number of readers in many countries. However, the growth rate, as well as the market penetration of e-books, varies considerably between countries and language areas. In the United States and other English-speaking countries, the use of e-books is more widespread than in many European countries, such as Sweden. In both the United States and Swedish markets, the growth rate has slowed down during the latest 2 years, and the majority of readers still seem to prefer printed books. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 23 publications
3
15
0
5
Order By: Relevance
“…The results of this study show that gender will influence the intention to use e-books. The results of this study are the same from Bergström and Höglund (2018) and Leitao et al (2018) revealed that gender can also be a determining factor in the choice of using printed or electronic books like women prefer reading and buying printed books when compared to electronic books or men are considered more familiar and accustomed to the use of technology when compared to women. Men are easier to adopt new technology than women (Ong and Lai, 2006; Daramola, 2013; Pratama, 2020) but in the research conduct by Smeda, Shiratudin and Wong (2017) show that female more confident in the use of the e-book.…”
Section: Discussion and Practical Implicationssupporting
confidence: 77%
See 2 more Smart Citations
“…The results of this study show that gender will influence the intention to use e-books. The results of this study are the same from Bergström and Höglund (2018) and Leitao et al (2018) revealed that gender can also be a determining factor in the choice of using printed or electronic books like women prefer reading and buying printed books when compared to electronic books or men are considered more familiar and accustomed to the use of technology when compared to women. Men are easier to adopt new technology than women (Ong and Lai, 2006; Daramola, 2013; Pratama, 2020) but in the research conduct by Smeda, Shiratudin and Wong (2017) show that female more confident in the use of the e-book.…”
Section: Discussion and Practical Implicationssupporting
confidence: 77%
“…An ebook format is an option, if you want to focus, then the printed book. Bergström and Höglund (2018) show that electronic books provide complementary functions not substitute functions of books. Research conducted by Wijayanta et al (2017) shows that with the use of e-books such as BSE in Indonesia, the average learning outcomes are better than those who do not use e-books.…”
Section: Discussion and Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Burkey, 2013;Have & Pedersen, 2015;Rubery, 2011;Th ompson, 2012;Wallin & Nolin, 2020). Whereas adoption of e-books has been slow (Bergström & Höglund, 2020), subscription-based audiobook services off er a reading experience that represent a shift in how and when books are read (Wallin & Nolin, 2020). Th is could imply a continued growth for book streaming services.…”
Section: Streaming Audiomentioning
confidence: 99%
“…Even for the younger generation, at least half of consumers had not read e-books. Thus, consumers still purchase both traditional paper books and e-books, depending on preferences, situations, and places (see, for instance, Bergström and Höglund (2020) for the recent trend in e-books in Sweden). We can see such co-existence of physical and digital content in the games, movies, and music industries.…”
Section: Introductionmentioning
confidence: 99%